Lithium Use in a Patient With Bipolar Disorder and End-Stage Kidney Disease on Hemodialysis: A Case Report - Chang, Cheryl W. L.; Ho, Cyrus S. H. (Frontiers in Psychiatry, 2020)
Lithium has been implicated in causing chronic tubulointerstitial nephritis and decline in renal function. However, lithium still plays a role in stabilizing patients with bipolar disorder. We illustrated a case of a bipolar I disorder patient approaching end-stage kidney disease (ESKD) with other medical comorbidities. As her mental state was affecting her compliance with medical treatment, she was mentally and medically unwell. Our patient was hospitalized on two separate occasions, for 5 and 4 months respectively, and failed adequate trials of different psychotropics due to inefficacy or intolerable side effects. A decision was made between the psychiatrist, nephrologist, and cardiologist to use lithium with hemodialysis support, with good treatment response and improved mental state. This case has shown that lithium carbonate can still be prescribed in ESKD patients on hemodialysis. Daily monitoring of lithium levels in the initial phase of lithium and hemodialysis commencement for at least 2 weeks is imperative, reducing to three times per week pre-hemodialysis towards the end of discharge after three consecutive daily serum lithium levels have stabilized. Clinicians can also consider a target serum level of less than 0.6 mEq/L in maintenance treatment for bipolar disorder in patients on hemodialysis.